THE ISLAND OF ELBA - NORTHERN TYRRHENIAN SEA AEROMAGNETIC AND GRAVITY DATA - Cassano, Emanuele; Anelli, Luigi; Cappelli, Vincenzo; Giori, Italiano; La Torre, Paolo (Ofioliti, 2007)
The magnetic maps of the northern Tyrrhenian Sea show anomalies belonging to bodies with high magnetic susceptibility, distributed according to a north-south trend over arcuate belts from the Elba area towards N-NW. A qualitative analysis of the anomalies shows that, among the high amplitude and short wave length anomalies, submarine ophiolites and/or volcanics occur.The high frequency anomalies connected with the ophiolites show a complex pattern, justified in the tectonic context of the area. Two main belts of ophiolites are identified: the inner (western) belt lies between the Corsica basin and the Capraia, Elba, and Pianosa islands; the external (eastern) one lies between the Gorgona, Elba islands and the Tuscan coast line.The volcanics consist of magmatic bodies (Miocene-Quaternary). Magnetic anomalies with longer wavelength, lower amplitude and low susceptibility are attributed to the magnetic basement.Based on the interpretation of the magnetic and gravity data, an appraisal of the tectonics of this area is presented, where both oceanic (ophiolites) and continental affinity crustal units occur, locally intruded by Pliocene granodioritic stocks.The main SW-NE discontinuities, crossing the Elba ridge and extending to onshore Tuscany, complete the structural framework of this sector of the Tyrrhenian Sea and the contiguous northern Apennine domain, as the result of the Mio-Pliocene and Pleistocene tectonics.